COMPOSIÇÃO QUÍMICA E AVALIAÇÃO DA ATIVIDADE CARRAPATICIDA DO ÓLEO ESSENCIAL DE Cinnamomun zeylanicum NO CONTROLE DE Rhipicephalus microplus - Monteiro, Ildenice Nogueira (2013)
The oil constituent of Cinnamomum zeylanicum were identified by gas chromatography-mass spectrometry (GC-MS). The essential oil activity were also evaluated against larvae and engorged females Rhipicephalus microplus(cattle tick). The leaves oil showed a yeld of 1.03% and its main constituints were benzyl benzoate (65.39%), linalool (5.37%), E-cinnamaldeyde (3.97%), α-Pinene (3.95%), β-phellandrene (3.42%), Eugenol (3.36%) e Benzaldeyde (2.68%), corresponding approximately to 88% of the oil. Test package larvae and immersion test of engorged were performed. Similar tests were also performed for the standard benzyl benzoate, the main component of the essential oil. Lethal concentrations of the larvae test were 1.005 mg.mLˉ¹ and 3.368 mg.mLˉ¹ for the essential oil and the standard benzyl benzoate respectively, thus demonstrating that the oil had a better larvicidal activity against the R. microplus. As for the adult immersion test, it was observed that both the essential oil and the standard benzyl benzoate did not cause mortality in direct engorged female R. microplus, but interfered with the process of reproduction of ticks, causing a decrease in egg production and decreased hatchability and mortality of larvae, so thus presenting partial control over the cattle tick.